Оцінка ефективності економічного механізму управління підприємством - Тімченко, Олена Олексанрівна; Черепанова, Вікторія Олександрівна (НТУ "ХПІ", 2015)
В статті розглядається сутність поняття «ефективність». Окреслено основні проблеми оцінки ефективності діяльності підприємства. Проаналізовано існуючі підходи та методи оцінки ефективності діяльності підприємства, їх особливості, переваги та недоліки, основні показники, які використовуються. Підкреслюється значимість урахування якісних показників для оцінки ефективності. Запропоновано комплексну систему оцінювання ефективності економічного механізму управління, яка базується на збалансованій системі показників (BSC).

The article deals with the evaluation of the enterprise effectiveness, which helps to indicate existing problems and eliminate them, what is essential for maintaining enterprise’s competitiveness, growth and development. An essence of the notions “efficiency” and “effectiveness” is considered. The main problems of the effectiveness evaluation of enterprise are outlined. The main approaches and methods of the effectiveness evaluation of enterprise, such as traditional resource-based approach, DuPont method, balanced scorecard technique and activity-based performance analysis (ABPA) are analyzed. Theirs characteristics, advantages and limitations, chief indicators used are described. An impotence of taking into consideration the qualitative indicators for evaluating the effectiveness is emphasized. A complex evaluation system for economic mechanism of management based on balanced scorecard (BSC) has been proposed.
Evaluation of the effectiveness for economic mechanism of enterprise management
Keywords: діяльність господарська; діяльність фінансова; модель "Дюпон"; traditional approach; DuPont model